2016
DOI: 10.1364/oe.24.028958
|View full text |Cite
|
Sign up to set email alerts
|

2f-wavelength modulation Fabry-Perot photothermal interferometry

Abstract: Trace gas detection was performed by the principle of photothermal interferometry using a Fabry-Perot interferometer combined with wavelength modulation and second harmonic detection. The sensor employed a compact, low-volume gas cell in an overall robust set-up without the use of any moveable part. A quantum cascade laser was used as powerful mid-infrared excitation source to induce refractive index changes in the sample, whereas a near-infrared laser diode served as probe source to monitor the photo-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…The detailed treatment of collisional energy transfers responsible for the generation of photoacoustic signals allows for the influence of a variety of experimental parameters such as pressure, humidity, or modulation frequency to be simulated and can hence help identify the preferred operation conditions in sensing applications. The model can be easily adapted, for example, to include oxygen as an important collision partner in ambient measurements, and is equally valid for photoacoustic and photothermal detection [29]. Finally, since the kinetic model yields rates for the collisional relaxation of CO, it can also be used to estimate the saturation intensity of CO at varying humidities and pressures [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…The detailed treatment of collisional energy transfers responsible for the generation of photoacoustic signals allows for the influence of a variety of experimental parameters such as pressure, humidity, or modulation frequency to be simulated and can hence help identify the preferred operation conditions in sensing applications. The model can be easily adapted, for example, to include oxygen as an important collision partner in ambient measurements, and is equally valid for photoacoustic and photothermal detection [29]. Finally, since the kinetic model yields rates for the collisional relaxation of CO, it can also be used to estimate the saturation intensity of CO at varying humidities and pressures [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…In Ref [59]., Waclawek et al proposed an FP-based PT gas with the layout shown in Figure 13. The FP interferometer was based on two dielectrically-coated silica mirrors with reflectivity R = 0.85, which resulted in a finesse of the cavity of 19.3.…”
Section: Fabry-perot Pt Gas Sensor With 2f Modulationmentioning
confidence: 99%
“…The work presented in Reference [59] was quickly followed by a second publication by the same Authors. In Reference [60], Waclawek et al addressed the main issues of their previous sensor and proposed a similar configuration, but enriched with balanced detection of the PT-induced intensity modulation of the beam leaking from the FP cavity.…”
Section: Balanced Detection Fabry-perot Pt Gas Sensormentioning
confidence: 99%
See 1 more Smart Citation
“…Gas detection techniques based on optical absorption have many advantages, such as fast response time, high gas selectivity, high measurement precision, no requirement for any sample pretreatment, and minimal drift. Hence, the tunable diode laser absorption spectroscopy (TDLAS) technique that employs a multi-pass gas cell (MGC) [ 8 ], the photo-acoustic spectroscopy (PAS) technique that employs a broadband microphone [ 9 ], the dispersion spectroscopy technique [ 10 ], and the photothermal interferometry technique [ 11 ] have been widely used in recent years. However, sensors based on MGC and PAS are large in size.…”
Section: Introductionmentioning
confidence: 99%